(untitled) (Global Scientific Review, 2023)
This work is devoted to the isolation of Vexibia alopecia des from the Fabacea family e physiologically active flavonoids and the possibility of synthesizing drugs used in medicine on their basis. As a result of the work, a flavonoid was isolated – in exibinol, its structure and properties were studied, and identified by IR, UV, PMR, NMR 13 methods of analysis.